Position Paper Number 2 for the Workshop “Towards Criteria of Sustainability and Social Meaningfulness in Development“: Critical Reflections on Modernization Theoretical Thinking and its Implications for ICTs in Development - Robert M. Bichler; Eva Gaderer (tripleC: Communication, Capitalism & Critique)
-